Impact of Hydrophobic Pollutants' Behavior on Occupational and Environmental Health - Ijeoma Kanu; Ebere Anyanwu (The Scientific World Journal)
This paper reviews the influence of hydrophobic pollutant behavior on environmental hazards and risks. The definition and examples of hydrophobic pollutants are given as a guide to better understand the sources of release and the media of dispersion in the environment. The properties and behavior of hydrophobic pollutants are described and their influence on environmental hazard and risk is reviewed and evaluated. The overall outcome of the assessment and evaluation showed that all hydrophobic pollutants are hazardous and risky to all organisms, including man. Their risk effects are due to their inherent persistence, bioaccumulation potential, environmental mobility, and reactivity. Their hazardous effects on organisms occur at varying spatial and temporal degrees of emissions, toxicities, exposures, and concentrations.